A highly sensitive fluorescent detection method utilizing B and S co-doped graphene quantum dots for ibuprofen analysis - Zheyi Geng (Alexandria Engineering Journal)
A highly sensitive and selective fluorescent probe utilizing B and S co-doped graphene quantum dots (BS-GQDs) has been created for detecting ibuprofen. The co-doping strategy effectively modulated the electronic structure and surface properties of GQDs, resulting in enhanced fluorescence quantum yield and sensing performance. The BS-GQDs exhibited strong fluorescence quenching upon interaction with ibuprofen, which was attributed to the formation of a ground-state complex and electron transfer from BS-GQDs to ibuprofen. Under optimal conditions, the sensor exhibited a broad linear range, a low detection limit, and outstanding selectivity for ibuprofen compared to other common medications and interferents. The practical utility of the sensor was validated through the successful identification of ibuprofen in spiked urine and serum samples, achieving high recovery rates and accuracy. The BS-GQDs-based fluorescent sensor provides a promising platform for sensitive, rapid, and reliable monitoring of ibuprofen in pharmaceutical and biomedical fields.